Control Strategy of Low-voltage Ride-through for Micro-grid under Asymmetric Grid Voltage - XU Liang; HAN Minxiao (Kongzhi Yu Xinxi Jishu)
It researched the control strategy of micro-grid low voltage ride-through under asymmetric grid voltage, established a mathematical model of micro- grid stability controller under asymmetric grid voltage for low voltage ride- through of micro-grid under asymmetric voltage sag, proposed a control strategy based on improved PR control for micro-grid low voltage ride- through. Simulation results show that the fault current of PCC can be reduced effectively by the issued control strategy.